Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.15404/msrj/03.2016.0005
|View full text |Cite
|
Sign up to set email alerts
|

Time to Neurological Deterioration in Ischemic Stroke

Abstract: Background-Neurological deterioration (ND) is common, with nearly one-half of ND patients deteriorating within the first 24 to 48 hours of stroke. The timing of ND with respect to ND etiology and reversibility has not been investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…In the present study, we defined ND as an increase of ≥2 points in the NIHSS score within 72 h of AIS occurrence, which is caused by ischemic area extension, recurrent stroke, or symptomatic intracerebral hemorrhagic transformation. This definition is similar to that of nonreversible ND reported by Siegler et al [31]. A large infarct area with brain edema and subsequent herniation during AIS was not considered an indicator of early ND in the present study.…”
Section: Discussionsupporting
confidence: 78%
“…In the present study, we defined ND as an increase of ≥2 points in the NIHSS score within 72 h of AIS occurrence, which is caused by ischemic area extension, recurrent stroke, or symptomatic intracerebral hemorrhagic transformation. This definition is similar to that of nonreversible ND reported by Siegler et al [31]. A large infarct area with brain edema and subsequent herniation during AIS was not considered an indicator of early ND in the present study.…”
Section: Discussionsupporting
confidence: 78%
“…The key links in the pathogenesis of cerebral ischemia are: lack of oxygenation of neurons, oppression of the aerobic and anaerobic pathways of glucose utilization in the brain, reduced energy production, violation of the transport of potentialdetermining ions, changes in the acid-base state, excitotoxicity, the occurrence of oxidative including nitrosative stress, involved nitric oxide (NO), activation of the inflammatory process, apoptosis. These processes cannot be modeled in vitro, and most research on ischemic brain injury are conducted on animals [2]. An analysis of literature data has revealed a wide range of different methods for modeling cerebral ischemia, which makes it possible to use methods that correspond the pursued goal and technical capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Existing evidence suggested that the mechanism might be related to new infarcts, hemorrhagic transformation, encephaledema, and onset of seizure. 4 6…”
Section: Introductionmentioning
confidence: 99%
“…Existing evidence suggested that the mechanism might be related to new infarcts, hemorrhagic transformation, encephaledema, and onset of seizure. 4,6 Furthermore, in AIS patients with large vessel occlusion suitable for MT therapy, the reperfusion rate for intravenous thrombolysis (IVT) was approximately 10%. 7 Therefore, in countries like the United States of America and China, MT is the therapy of choice for stroke patients with large artery occlusion.…”
Section: Introductionmentioning
confidence: 99%